2017
DOI: 10.1002/humu.23356
|View full text |Cite
|
Sign up to set email alerts
|

Whole exome and whole genome sequencing with dried blood spot DNA without whole genome amplification

Abstract: Newborn screening (NBS) for rare conditions is performed in all 50 states in the USA. We have partnered with the California Department of Public Health Genetic Disease Laboratory to determine whether sufficient DNA can be extracted from archived dried blood spots (DBS) for nextgeneration sequencing in the hopes that next-generation sequencing can play a role in NBS. We optimized the DNA extraction and sequencing library preparation protocols for residual infant DBS archived over 20 years ago and successfully o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 9 publications
0
37
0
Order By: Relevance
“…Dried blood spots are potential resources for genetic and genomic analysis. Recent studies showed that sufficient DBS DNA can be extracted and used for NGS to perform whole exome sequencing (WES) and whole genome sequencing (WGS) without genome amplification ( 45 ). The use of next-generation sequencing has the potential to be integrated in SCID NBS programs to facilitate and accelerate genetic testing and final diagnosis of affected newborns.…”
Section: Discussionmentioning
confidence: 99%
“…Dried blood spots are potential resources for genetic and genomic analysis. Recent studies showed that sufficient DBS DNA can be extracted and used for NGS to perform whole exome sequencing (WES) and whole genome sequencing (WGS) without genome amplification ( 45 ). The use of next-generation sequencing has the potential to be integrated in SCID NBS programs to facilitate and accelerate genetic testing and final diagnosis of affected newborns.…”
Section: Discussionmentioning
confidence: 99%
“…Addition of new diseases to NBS panels can be expected to reveal both anticipated information on disease incidence, spectrum and characteristics and unanticipated findings that challenge medical experts and engage basic scientists. Moreover, storage of residual DBS material collected for NBS opens the possibility of conducting much more far‐reaching research, while with modern DNA sequencing technology one can sequence a person's entire genome using a small punch from a stored DBS . Controversies and legal battles claiming breaches of the public trust have resulted in destruction of state biobanks of newborn DBS.…”
Section: Screening For Scid As a Public Health Measurementioning
confidence: 99%
“…Moreover, storage of residual DBS material collected for NBS opens the possibility of conducting much more far-reaching research, while with modern DNA sequencing technology one can sequence a person's entire genome using a small punch from a stored DBS. 21 Controversies and legal battles claiming breaches of the public trust have resulted in destruction of state biobanks of newborn DBS.…”
Section: Screening For Scid a S A Pub Lic He Alth Me A Surementioning
confidence: 99%
“…DNA extraction, library preparation and sequencing were carried out following a previously described protocol. (Bassaganyas, et al, 2018) The reads from the NBSeq exomes were mapped to the human reference genome GRCh37 assembly (Aug 2009 release), using BWA-mem v0.7.10 ( Li and Durbin, 2009). The resulting BAM files were sorted, indexed and marked for PCR duplicate reads by Picard v0.7.10 (http://picard.sourceforge.net).…”
Section: Exome Sequencing and Analysismentioning
confidence: 99%